Research on Dynamic Response of Shallow Buried Tunnel Lining Constructed by Drilling and Blasting Method - Bo Wu; Yaozhong Cui; Guowang Meng; Shixiang Xu; Chengming Xia; Yicai Li; Yao Zhang (Advances in Materials Science and Engineering)
To study the dynamic response of shallow buried tunnel lining by drilling and blasting method, ABAQUS simulation software was used to establish a tunnel blasting finite element model based on the consideration of in situ stress. Dynamic static coupling numerical simulation was conducted to analyze the vibration response and stress response of tunnel lining. The simulation results were compared and analyzed with field monitoring data to obtain the dynamic response law of tunnel lining. The results show that in the same tunnel lining section, the vibration velocity response in the Y direction is the largest and the vibration velocity response in the Z direction is the smallest. The location of the peak particle velocity of the tunnel lining in three directions appears differently, and the location of the maximum MISES stress appears differently for different excavation sections. The arch shoulder is most affected by horizontal vibration in the X direction, and the vault is most affected by horizontal vibration in the Y direction. The dynamic response at the foot or arch shoulder position away from the lining section of the working face will show the “whip tip effect.” A sudden change in MISES stress occurs at the location of the footing in the 315° direction of the liner section, and the liner is not uniformly stressed in this range.